GAMBARAN PELAKSANAAN KEWASPADAAN UNIVERSAL DI RUMAH SAKIT UMUM DAERAH Dr MOEWARDI SURAKARTA - Sri Hunun Parsinahingsih (Universitas Muhammadiyah Surakarta, 2008)
Universal care research RSUD DR. Moewardi Surakarta has a perfect background that one of serve nurse parameter with a good quality in hospital was with infection Nosokomial control. Injection moment has a tight relationship with professional nurse practice with a universal care.This research purposes was to know about the act of hand washing to prevent the cross infection and to know about appliance protect uses, to know about sharp appliance and needle use, to know about dirty waste and sanitation. This is a descriptive research with 55 nurses, research method using observation which is done with 5 observers as room’s leader.The result of this research, 55 respondent will have 16,4% nurse education was SPK graduating, 74,5% AKPER Grad from nurse education, 9,1% nurse education was a nurse Master Grad, as a universal act precations is got 15% nurse doing hand wash imperfectly, 80% nurse doing hand wash perfectly and 5% nurse doesn’t doing hand wash. 20% nurse use a imperfect protection appliance, 71% nurse use a perfect protection appliance and 9% nurse doesn’t use a perfect protection appliance. 15% nurse managing the imperfect second hands health appliance, 79% nurse managing the second hands health appliance perfectly and 6% nurse doesn’t managing the second hands health appliance. 18% nurse managing the imperfect needle or sharp appliance, 72% nurse managing needle or sharp appliance perfectly and 10% nurse doesn’t managing needle or sharp appliance. 13% nurse managing the dirty waste or room sanitation imperfectly, 80% nurse managing dirty waste or room sanitation perfectly and 7% nurse doesn’t managing dirty waste or room sanitation. The conclusion there is still a nurse who is done a universal care imperfectly either doesn’t doing. It needs socialization about a hand book (SOP) universal care and the relaxation about universal care.